2021
DOI: 10.2196/21977
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mobile Health and Self-Management App for High-Risk Patients With Chronic Obstructive Pulmonary Disease in Daily Clinical Practice: Mixed Methods Evaluation Study

Abstract: Background Mobile health and self-management interventions may positively affect behavioral change and reduce hospital admissions for patients with chronic obstructive pulmonary disease (COPD). However, not all patients qualify for these interventions, and systematic, comprehensive information on implementation- and compliance-related aspects of mobile self-management apps is lacking. Due to the tendency to target digital services to patients in stable phases of disease, it is especially relevant t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 53 publications
4
43
0
2
Order By: Relevance
“…In adults, technology-enabled patient education showed an increased disease specific knowledge [12,21] and inhaler technique improved [13]. The perception of coping with the condition also increased [12]. Although not all studies found increases, reported no change in COPD knowledge [11].…”
Section: Gain Of Skills and Knowledgementioning
confidence: 96%
See 4 more Smart Citations
“…In adults, technology-enabled patient education showed an increased disease specific knowledge [12,21] and inhaler technique improved [13]. The perception of coping with the condition also increased [12]. Although not all studies found increases, reported no change in COPD knowledge [11].…”
Section: Gain Of Skills and Knowledgementioning
confidence: 96%
“…A significant increase in measuring learning outcomes has occurred in the last decade with 6 of the 13 studies evaluating gain of skills, knowledge, and attitudes. In adults, technology-enabled patient education showed an increased disease specific knowledge [12,21] and inhaler technique improved [13]. The perception of coping with the condition also increased [12].…”
Section: Gain Of Skills and Knowledgementioning
confidence: 98%
See 3 more Smart Citations